Human capital, creative class and regional economic performance: A dynamic panel analysis - Esubalew Alehegn; Silvia Sacchetti; Ermanno Tortia (Economics and Econometrics Research Institute (EERI), 2013)
Though the measurement and implication of human capital on economic growth has been well established since the works of Becker in the 1960s, recently Florida has argued that creative class is superior to human capital in explaining economic growth. The underlying difference between the two scholars is a measurement approach in which while Becker uses education as indicator of human capital Florida employs occupation as an identifier of the creative class. We exploit administrative data from the Institute for Employment Research (IAB) over the years 1998-2008 and employ system GMM to estimate and compare the effects on regional economic performance of human capital and creative class in Germany where economic performance is measured by GDP growth, employment growth and wage growth. The estimation unveils that analysis of regional economy through creative class in place of human capital can be used as an alternative approach yet the creative class, as has been praised by Florida, is not found to be superior to human capital in explicating economic performance of regions. Indeed, albeit the share of creative class (creative core and creative professionals) and university graduates have positive and robust impacts on GDP growth it is by no means the share of university graduates that have a far greater impact on economic growth. The opposite holds for employment growth and is inconclusive for wage growth. This finding may imply that the creative class driven economic development is directed towards more labor intensive forms of development whilst human capital is directed towards the form of development characterized by specialization and high capital intensity.
Keywords: R11; O31; O52; 330; Creative class; human capital; economic performance and dynamic panel